2019
DOI: 10.2147/idr.s202386
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diffuse multibacillary leprosy patient with Lucio&rsquo;s phenomenon and positive anticardiolipin antibody misdiagnosed as lupus erythematosus panniculitis in the People&rsquo;s Republic of China</p>

Abstract: Lucio’s phenomenon (LP) is a special reactional state associated with diffuse multibacillary leprosy; both exhibit a limitative global distribution mainly in Mexico and Central America. We report a case of a 28-year-old female leprosy patient in the People's Republic of China, together with LP and positive anticardiolipin antibody, characterized by vascular thrombosis and invasion of blood vessel walls by leprosy bacilli, causing extensive skin ulcers and followed by a large number of atrophic scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The reason the anti-phospholipid antibody (IgG-IgM) concentration increase in the miscarriage women and the pregnancy failure group may be because coagulation syndrome is a blood clotting disorder that causes blood to clot in the capillaries, which may be because of the lack of blood flow and into the uterus, This leads to a weak endometrium, and thus, reduces fetal consistency in the uterus, which increases the possibility of miscarriage or pregnancy failure, while in the case of continuing the pregnancy (control group). The anti-phospholipid antibody (IgG-IgM) level is low, which means that no thrombus in the capillaries, and thus the blood flow is normal and therefore so that the fetus is a strong adhesion due to the strength of the inner lining of the uterus, which leads to the lack of miscarriage, and these results are consistent with other researches (Gao et al ., 2019 ) and (Mansour et al ., 2020) they showed that the increase in the level of anti-phospholipids antibody (IgG-IgM) in aborted women during the first trimester of pregnancy, compared with non-pregnant women, was about 15 %.…”
Section: Discussionsupporting
confidence: 88%
“…The reason the anti-phospholipid antibody (IgG-IgM) concentration increase in the miscarriage women and the pregnancy failure group may be because coagulation syndrome is a blood clotting disorder that causes blood to clot in the capillaries, which may be because of the lack of blood flow and into the uterus, This leads to a weak endometrium, and thus, reduces fetal consistency in the uterus, which increases the possibility of miscarriage or pregnancy failure, while in the case of continuing the pregnancy (control group). The anti-phospholipid antibody (IgG-IgM) level is low, which means that no thrombus in the capillaries, and thus the blood flow is normal and therefore so that the fetus is a strong adhesion due to the strength of the inner lining of the uterus, which leads to the lack of miscarriage, and these results are consistent with other researches (Gao et al ., 2019 ) and (Mansour et al ., 2020) they showed that the increase in the level of anti-phospholipids antibody (IgG-IgM) in aborted women during the first trimester of pregnancy, compared with non-pregnant women, was about 15 %.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, prognosis and mortality are variable due to not many of the cases that have been reported [3,5] . Gao et al [11] result combination MDT-MB with prednisolone 1 mg/kg/day caused partial resolution of skin lesion. Some literature reported thalidomide and pentoxifylline are accepted for the FL cases as well [7,12] .…”
Section: Casementioning
confidence: 96%
“…Histopathological examination was obtained from a skin biopsy and will show are a granulomatous inflammation (foamy macrophage cells or Virchow cells), epidermal and dermal necrosis, endothelial proliferation, vasculitis, obliteration, occlusion of the lumen and thrombosis of medium sized blood vessels in the superficial and mid dermis. In AFB and Fite-Farco staining, M. leprae colonization was found on endothelial, interstitial, and foam cells [2][3][4][5][6][11][12] . A study conducted in Malaysia reported that up to 44% of LP cases seen initially in primary care were misdiagnosed [3] .…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations